2021
DOI: 10.1002/ppp3.10179
|View full text |Cite
|
Sign up to set email alerts
|

Can arbuscular mycorrhizal fungi speed up carbon sequestration by enhanced weathering?

Abstract: Climate change is one of the most pressing environmental and societal issues currently faced by humanity (IPCC, 2018). At the 2015 climate summit in Paris, nearly all world leaders committed themselves to limit global warming to well below 2°C (UNFCCC, 2015). Achieving this target requires rapid and complete decarbonization of all sectors. Current policies focus on conventional mitigation to reduce emissions, yet scenario analyses and model projections unveiled that conventional mitigation alone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…Various researchers have confirmed that orchards like citrus, wine grape, apple, olive, peach, hazelnut, and orange could be a substantial sink for atmospheric carbon (Liguori et al, 2009;Granata et al, 2020). Similarly, any agricultural practices, like the use of organic manures or AM fungi, may act as carbon sinks (Shi et al, 2017;Sharma et al, 2018;Verbruggen et al, 2021). Several studies have shown that the application of organic manures improves the physicochemical properties of soil (Evanylo et al, 2008;Bravo et al, 2012;Sharma et al, 2018;Sharma et al, 2021) and ameliorates root development (Baldi et al, 2010;Sarita et al, 2019).…”
Section: Carbon Capture Of Long Residence Woody Leaf Fruit and Rootsmentioning
confidence: 99%
“…Various researchers have confirmed that orchards like citrus, wine grape, apple, olive, peach, hazelnut, and orange could be a substantial sink for atmospheric carbon (Liguori et al, 2009;Granata et al, 2020). Similarly, any agricultural practices, like the use of organic manures or AM fungi, may act as carbon sinks (Shi et al, 2017;Sharma et al, 2018;Verbruggen et al, 2021). Several studies have shown that the application of organic manures improves the physicochemical properties of soil (Evanylo et al, 2008;Bravo et al, 2012;Sharma et al, 2018;Sharma et al, 2021) and ameliorates root development (Baldi et al, 2010;Sarita et al, 2019).…”
Section: Carbon Capture Of Long Residence Woody Leaf Fruit and Rootsmentioning
confidence: 99%
“…The weathering rate of silicate minerals depends on several abiotic and biotic factors. Specifically, it increases with increasing surface area (Strefler et al, 2018), while higher pH, lower temperature, and precipitation rates, along with varying soil CO 2 partial pressure can negatively affect the weathering rates (Verbruggen et al, 2021). Biogeochemical and biomechanical activity can also affect weathering rates in soils (Vicca et al, 2022).…”
Section: Enhanced Weathering In Soilsmentioning
confidence: 99%
“…Biogeochemical and biomechanical activity can also affect weathering rates in soils (Vicca et al, 2022). Plants may enhance silicate mineral weathering in soils through their roots and associated mycorrhizal fungi, via diverse mechanisms such as the release of organic acids (Taylor et al, 2009;Thorley et al, 2015;Verbruggen et al, 2021) and secretion of acids or stimulation of acid-generating nitrification by nitrogen-fixing plants (Bolan et al, 1991;Epihov et al, 2017;Perakis and Pett-Ridge, 2019). Invertebrates in soil also contribute to weathering, both chemically, through the action of gut microbiota, and mechanically by biopedturbation (Van Groenigen et al, 2019;Vicca et al, 2022).…”
Section: Enhanced Weathering In Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that mycorrhizal fungi depend on their host for C, their influence on ESW is likely to be strongly related to plant activity and plant C allocation. Depending on soil conditions, plants can allocate substantial amounts of C to mycorrhizal fungi (Ven et al, 2020), and thereby stimulate their weathering activity, increasing the release of P and other mineral elements from the silicate minerals (Verbruggen et al, 2021).…”
Section: Biota Stimulating Silicate Weatheringmentioning
confidence: 99%